Identification of Nuclearity of Chromium Binary Adducts with DNA by Negative Ion Mass Spectrometry: Short Communication - Kaleb Kovitch; Qiaoli Liang; Katie Repke; Elizabeth K. Atkinson; Stephen A. Woski; John B. Vincent (Biological Trace Element Research, 2025)

Icing‐related injuries in polar bears ( Ursus maritimus ) at high latitudes - Kristin L. Laidre; Stephen N. Atkinson (Ecology, 2024)

Mechanistic safety assessment via multi-omic characterisation of systemic pathway perturbations following in vivo MAT2A inhibition - Valentina Fogal; Filippos Michopoulos; Andrew F. Jarnuczak; Ghaith M. Hamza; Stephanie Harlfinger; Paul Davey; Heather Hulme; Stephen J. Atkinson; Piotr Gabrowski; Tony Cheung; Michael Grondine; Clare Hoover; et al. (Archives of Toxicology, 2024)
The tumour suppressor p16/CDKN2A and the metabolic gene, methyl-thio-adenosine phosphorylase (MTAP), are frequently co-deleted in some of the most aggressive and currently untreatable cancers. Cells with MTAP deletion are vulnerable to inhibition of the metabolic enzyme, methionine-adenosyl transferase 2A (MAT2A), and the protein arginine methyl transferase (PRMT5). This synthetic lethality has paved the way for the rapid development of drugs targeting the MAT2A/PRMT5 axis. MAT2A and its liver- and pancreas-specific isoform, MAT1A, generate the universal methyl donor S-adenosylmethionine (SAM) from ATP and methionine. Given the pleiotropic role SAM plays in methylation of diverse substrates, characterising the extent of SAM depletion and downstream perturbations following MAT2A/MAT1A inhibition (MATi) is critical for safety assessment. We have assessed in vivo target engagement and the resultant systemic phenotype using multi-omic tools to characterise response to a MAT2A inhibitor (AZ’9567). We observed significant SAM depletion and extensive methionine accumulation in the plasma, liver, brain and heart of treated rats, providing the first assessment of both global SAM depletion and evidence of hepatic MAT1A target engagement. An integrative analysis of multi-omic data from liver tissue identified broad perturbations in pathways covering one-carbon metabolism, trans-sulfuration and lipid metabolism. We infer that these pathway-wide perturbations represent adaptive responses to SAM depletion and confer a risk of oxidative stress, hepatic steatosis and an associated disturbance in plasma and cellular lipid homeostasis. The alterations also explain the dramatic increase in plasma and tissue methionine, which could be used as a safety and PD biomarker going forward to the clinic.

Exotic myxozoan parasites establish complex life cycles in farm pond aquaculture - Barbara Salti; Stephen D. Atkinson; Vera Brekhman; Margarita Smirnov; Tamar Lotan (Journal of Invertebrate Pathology, 2024)

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Litter breakdown among intermittently connected and unconnected geographically isolated Wetlands: how nutrient inputs alter wetland function - Chelsea R. Smith; Stephen W. Golladay; Carla L. Atkinson; Brian A. Clayton (Wetlands, 2022)

Terrestrial ecosystem restoration increases biodiversity and reduces its variability, but not to reference levels: A global meta‐analysis - Joe Atkinson; Lars A. Brudvig; Max Mallen‐Cooper; Shinichi Nakagawa; Angela T. Moles; Stephen P. Bonser (Ecology Letters, 2022)
Ecological restoration projects often have variable and unpredictable outcomes, and these can limit the overall impact on biodiversity. Previous syntheses have investigated restoration effectiveness by comparing average restored conditions to average conditions in unrestored or reference systems. Here, we provide the first quantification of the extent to which restoration affects both the mean and variability of biodiversity outcomes, through a global meta‐analysis of 83 terrestrial restoration studies. We found that, relative to unrestored (degraded) sites, restoration actions increased biodiversity by an average of 20%, while decreasing the variability of biodiversity (quantified by the coefficient of variation) by an average of 14%. As restorations aged, mean biodiversity increased and variability decreased relative to unrestored sites. However, restoration sites remained, on average, 13% below the biodiversity of reference (target) ecosystems, and were characterised by higher (20%) variability. The lower mean and higher variability in biodiversity at restored sites relative to reference sites remained consistent over time, suggesting that sources of variation (e.g. prior land use, restoration practices) have an enduring influence on restoration outcomes. Our results point to the need for new research confronting the causes of variability in restoration outcomes, and close variability and biodiversity gaps between restored and reference conditions.

The Role of Satellite Telemetry Data in 21st Century Conservation of Polar Bears (Ursus maritimus) - Kristin L. Laidre; George M. Durner; Nicholas J. Lunn; Eric V. Regehr; Todd C. Atwood; Karyn D. Rode; Jon Aars; Heli Routti; Øystein Wiig; Markus Dyck; Evan S. Richardson; Stephen Atkinson; et al. (Frontiers in Marine Science, 2022)
Satellite telemetry (ST) has played a critical role in the management and conservation of polar bears ( Ursus maritimus ) over the last 50 years. ST data provide biological information relevant to subpopulation delineation, movements, habitat use, maternal denning, health, human-bear interactions, and accurate estimates of vital rates and abundance. Given that polar bears are distributed at low densities over vast and remote habitats, much of the information provided by ST data cannot be collected by other means. Obtaining ST data for polar bears requires chemical immobilization and application of a tracking device. Although immobilization has not been found to have negative effects beyond a several-day reduction in activity, over the last few decades opposition to immobilization and deployment of satellite-linked radio collars has resulted in a lack of current ST data in many of the 19 recognized polar bear subpopulations. Here, we review the uses of ST data for polar bears and evaluate its role in addressing 21 st century conservation and management challenges, which include estimation of sustainable harvest rates, understanding the impacts of climate warming, delineating critical habitat, and assessing potential anthropogenic impacts from tourism, resource development and extraction. We found that in subpopulations where ST data have been consistently collected, information was available to estimate vital rates and subpopulation density, document the effects of sea-ice loss, and inform management related to subsistence harvest and regulatory requirements. In contrast, a lack of ST data in some subpopulations resulted in increased bias and uncertainty in ecological and demographic parameters, which has a range of negative consequences. As sea-ice loss due to climate warming continues, there is a greater need to monitor polar bear distribution, habitat use, abundance, and subpopulation connectivity. We conclude that continued collection of ST data will be critically important for polar bear management and conservation in the 21 st century and that the benefits of immobilizing small numbers of individual polar bears in order to deploy ST devices significantly outweigh the risks.

An on-ice aerial survey of the Kane Basin polar bear (Ursus maritimus) subpopulation - Øystein Wiig; Stephen N. Atkinson; Erik W. Born; Seth Stapleton; Todd Arnold; Markus Dyck; Kristin L. Laidre; Nicholas J. Lunn; Eric V. Regehr (Polar Biology, 2022)
There is an imminent need to collect information on distribution and abundance of polar bears ( Ursus maritimus ) to understand how they are affected by the ongoing decrease in Arctic sea ice. The Kane Basin (KB) subpopulation is a group of high-latitude polar bears that ranges between High Arctic Canada and NW Greenland around and north of the North Water polynya (NOW). We conducted a line transect distance sampling aerial survey of KB polar bears during 28 April–12 May 2014. A total of 4160 linear kilometers were flown in a helicopter over fast ice in the fjords and over offshore pack ice between 76° 50′ and 80° N′. Using a mark-recapture distance sampling protocol, the estimated abundance was 190 bears (95% lognormal CI: 87–411; CV 39%). This estimate is likely negatively biased to an unknown degree because the offshore sectors of the NOW with much open water were not surveyed because of logistical and safety reasons. Our study demonstrated that aerial surveys may be a feasible method for obtaining abundance estimates for small subpopulations of polar bears.

Correction to: Experimental determination of the temperature dependence of oxygen-isotope fractionation between water and chitinous head capsules of chironomid larvae - Alex Lombino; Tim Atkinson; Stephen J. Brooks; Darren R. Gröcke; Jonathan Holmes; Vivienne J. Jones; Jim D. Marshall (Journal of Paleolimnology, 2021)

Experimental determination of the temperature dependence of oxygen-isotope fractionation between water and chitinous head capsules of chironomid larvae - Alex Lombino; Tim Atkinson; Stephen J. Brooks; Darren R. Gröcke; Jonathan Holmes; Vivienne J. Jones; Jim D. Marshall (Journal of Paleolimnology, 2021)
Oxygen-isotope values of invertebrate cuticle preserved in lake sediments have been used in palaeoenvironmental reconstructions, generally with the assumption that fractionation of oxygen isotopes between cuticle and water ( $$\upalpha_{\text{cuticle}-\text{H}_{2}\text{O}}$$ α cuticle - H 2 O ) is independent of temperature. We cultured chironomid larvae in the laboratory with labelled oxygen-isotope water and across a range of closely controlled temperatures from 5 to 25 °C in order to test the hypothesis that fractionation of oxygen isotopes between chironomid head capsules and water ( $$\upalpha_{\text{chironomid}-\text{H}_{2}\text{O}}$$ α chironomid - H 2 O ) is independent of temperature. Results indicate that the hypothesis can be rejected, and that $$\upalpha_{\text{chironomid}-\text{H}_{2}\text{O}}$$ α chironomid - H 2 O decreases with increasing temperature. The scatter in the data suggests that further experiments are needed to verify the relationship. However, these results indicate that temperature-dependence of $$\upalpha_{\text{chironomid}-\text{H}_{2}\text{O}}$$ α chironomid - H 2 O should be considered when chironomid δ 18 O is used as a paleoenvironmental proxy, especially in cases where data from chironomids are combined with oxygen-isotope values from other materials for which fractionation is temperature dependent, such as calcite, in order to derive reconstructions of past water temperature.

Proteomic Analysis of the Parasitic Cnidarian Ceratonova shasta (Cnidaria: Myxozoa) Reveals Diverse Roles of Actin in Motility and Spore Formation - Vera Brekhman; Maya Ofek-Lalzar; Stephen D. Atkinson; Gema Alama-Bermejo; Keren Maor-Landaw; Assaf Malik; Jerri L. Bartholomew; Tamar Lotan (Frontiers in Marine Science, 2021)
Myxozoans are widely distributed aquatic obligate endoparasites that were recently recognized as belonging within the phylum Cnidaria. They have complex life cycles with waterborne transmission stages: resistant, infectious spores that are unique to myxozoans. However, little is known about the processes that give rise to these transmission stages. To understand the molecular underpinnings of spore formation, we conducted proteomics on Ceratonova shasta , a highly pathogenic myxozoan that causes severe mortalities in wild and hatchery-reared salmonid fishes. We compared proteomic profiles between developmental stages from inside the fish host, and the mature myxospore, which is released into the water where it drifts passively, ready to infect the next host. We found that C. shasta contains 2,123 proteins; representing the first proteomic catalog of a myxozoan myxospore. Analysis of proteins differentially expressed between developing and mature spore stages uncovered processes that are active during spore formation. Our data highlight dynamic changes in the actin cytoskeleton, which provides myxozoan developmental stages with mobility through lamellipodia and filopodia, whereas in the mature myxospore the actin network supports F-actin stabilization that reinforces the transmission stage. These findings provide molecular insight into the myxozoan life cycle stages and, particularly, into the process of sporogenesis.

Progressive decline of T and B cell numbers and function in a patient with CDC42 deficiency - Paria Kashani; Ashish Marwaha; Stephen Feanny; Vy Hong-Diep Kim; Adelle R. Atkinson; Matilde Leon-Ponte; Roberto Mendoza-Londono; Eyal Grunebaum (Immunologic Research, 2021)

Transient benefits of climate change for a high‐Arctic polar bear ( Ursus maritimus ) subpopulation - Kristin L. Laidre; Stephen N. Atkinson; Eric V. Regehr; Harry L. Stern; Erik W. Born; Øystein Wiig; Nicholas J. Lunn; Markus Dyck; Patrick Heagerty; Benjamin R. Cohen (Global Change Biology, 2020)
Kane Basin (KB) is one of the world's most northerly polar bear ( Ursus maritimus ) subpopulations, where bears have historically inhabited a mix of thick multiyear and annual sea ice year‐round. Currently, KB is transitioning to a seasonally ice‐free region because of climate change. This ecological shift has been hypothesized to benefit polar bears in the near‐term due to thinner ice with increased biological production, although this has not been demonstrated empirically. We assess sea‐ice changes in KB together with changes in polar bear movements, seasonal ranges, body condition, and reproductive metrics obtained from capture–recapture (physical and genetic) and satellite telemetry studies during two study periods (1993–1997 and 2012–2016). The annual cycle of sea‐ice habitat in KB shifted from a year‐round ice platform (~50% coverage in summer) in the 1990s to nearly complete melt‐out in summer ( p = .004). Between the 1990s and 2010s, adult female (AF) seasonal ranges more than doubled in spring and summer and were significantly larger in all months. Body condition scores improved for all ages and both sexes. Mean litter sizes of cubs‐of‐the‐year (C0s) and yearlings (C1s), and the number of C1s per AF, did not change between decades. The date of spring sea‐ice retreat in the previous year was positively correlated with C1 litter size, suggesting smaller litters following years with earlier sea‐ice breakup. Our study provides evidence for range expansion, improved body condition, and stable reproductive performance in the KB polar bear subpopulation. These changes, together with a likely increasing subpopulation abundance, may reflect the shift from thick, multiyear ice to thinner, seasonal ice with higher biological productivity. The duration of these benefits is unknown because, under unmitigated climate change, continued sea‐ice loss is expected to eventually have negative demographic and ecological effects on all polar bears.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Identifying shifts in maternity den phenology and habitat characteristics of polar bears (Ursus maritimus) in Baffin Bay and Kane Basin - Erica Escajeda; Kristin L. Laidre; Erik W. Born; Øystein Wiig; Stephen Atkinson; Markus Dyck; Steven H. Ferguson; Nicholas J. Lunn (Polar Biology, 2018)

Occurrence of two novel actinospore types (Cnidaria: Myxosporea) in Brazilian fish farms, and the creation of a novel actinospore collective group, Seisactinomyxon - Tiago Milanin; Stephen D. Atkinson; Márcia R.M. Silva; Roberto G. Alves; Antônio A.M. Maia; Edson A. Adriano (Acta Parasitologica, 2017)
The involvement of oligochaetes in the life cycles of fresh water myxozoan parasites in Brazil was investigated. Of 333 oligochaetes collected in a fish farm in the State of São Paulo, three (0.9%) released Aurantiactinomyxon type spores. From 86 worms collected in a fish farm in Mato Grosso do Sul State, 1 (0.9%) released actinospores with a novel morphology for which we propose the name Seisactinomyxon. Infected oligochaetes were identified by morphology: all belonged to family Naididae, with

Reconstructing the confluence zone between Laurentide and Cordilleran ice sheets along the Rocky Mountain Foothills, south‐west Alberta - Daniel J. Utting; Nigel Atkinson; Steven Pawley; Stephen J. Livingstone (Journal of Quaternary Science, 2016)
Landform mapping near the Athabasca valley was fundamental to determining whether the Late Wisconsinan Laurentide and Cordilleran Ice Sheets (LIS, CIS) coalesced. In this paper we examine the detailed landform record using new LiDAR digital elevation and hillshade models of the area of confluence and eventual desuturing of these ice sheets. This work reveals an earlier more extensive Cordilleran advance before coalescence with the LIS. When the ice sheets coalesced, the flow pattern was dominated by ice flow along the mountain front, with Cordilleran ice flowing out of major trunk valleys but Laurentide ice flowing into the Foothills up smaller valleys. This flow pattern implies that when the ice sheets coalesced the CIS was already waning, or at least was not at its maximum. Deglaciation was interrupted by several re‐advances, probably related to the destabilizing effect of proglacial lakes along the ice margin.

Regime shifts in demersal assemblages of the Benguela Current Large Marine Ecosystem: a comparative assessment - Stephen P. Kirkman; Dawit Yemane; Lara J. Atkinson; John Kathena; Silvi E. Nsiangango; Larvika Singh; Bjorn E. Axelsen; Toufiek Samaai (Fisheries Oceanography, 2015)
Using long‐term survey data, changes in demersal faunal communities in the Benguela Current Large Marine Ecosystem were analysed at community and population levels to provide a comparative overview of the occurrence and timing of regime shifts. For South Africa, the timing of a community‐level shift observed in the early 1990s, and of a lesser shift observed in the mid‐2000s, corresponded well with the results of other studies that showed environmental, community‐level or population‐level changes at similar times, suggesting that environmental forcing had played a role. Several population‐level shifts were detected for Namibia; these and a regime shift in the overall community identified for this country corresponded well to the timing of severe environmental perturbations and an extensive regime shift in the pelagic ecosystem of this area. However, the interpretation of these shifts was confounded by changes in sampling gear; closer scrutiny of the types of species affected and the direction of shifts (increase/decrease) in relation to the timing and nature of sampling gear modifications, revealed that the observed shifts were potentially an artefact of gear changes. This highlighted the importance of accounting for changes in sampling protocols during the analysis and interpretation of long‐term data. For Angola, a community level shift in the mid‐2000s and population‐level changes for a few species (mainly positive), could not have been influenced by gear changes which took place mainly before the onset of the time series under consideration. However, no clear environmental or anthropogenic changes that could have influenced these shifts were obvious.

Fuelling for the Sahara crossing: variation in site use and the onset and rate of spring mass gain by 38 Palearctic migrants in the western Sahel - Nicholas J. Bayly; Philip W. Atkinson; Stephen J. R. Rumsey (Journal of Ornithology, 2012)

Water Quality and Planktonic Microbial Assemblages of Isolated Wetlands in an Agricultural Landscape - Carla L. Atkinson; Stephen W. Golladay; Matthew R. First (Wetlands, 2011)

Seabed foraging by Antarctic krill: Implications for stock assessment, bentho‐pelagic coupling, and the vertical transfer of iron - Katrin Schmidt; Angus Atkinson; Sebastian Steigenberger; Sophie Fielding; Margaret C. M. Lindsay; David W. Pond; Geraint A. Tarling; Thor A. Klevjer; Claire S. Allen; Stephen Nicol; Eric P. Achterberg (Limnology and Oceanography, 2011)
A compilation of more than 30 studies shows that adult Antarctic krill ( Euphausia superba ) may frequent benthic habitats year‐round, in shelf as well as oceanic waters and throughout their circumpolar range. Net and acoustic data from the Scotia Sea show that in summer 2‐20% of the population reside at depths between 200 and 2000 m, and that large aggregations can form above the seabed. Local differences in the vertical distribution of krill indicate that reduced feeding success in surface waters, either due to predator encounter or food shortage, might initiate such deep migrations and results in benthic feeding. Fatty acid and microscopic analyses of stomach content confirm two different foraging habitats for Antarctic krill: the upper ocean, where fresh phytoplankton is the main food source, and deeper water or the seabed, where detritus and copepods are consumed. Krill caught in upper waters retain signals of benthic feeding, suggesting frequent and dynamic exchange between surface and seabed. Krill contained up to 260 nmol iron per stomach when returning from seabed feeding. About 5% of this iron is labile, i.e., potentially available to phytoplankton. Due to their large biomass, frequent benthic feeding, and acidic digestion of particulate iron, krill might facilitate an input of new iron to Southern Ocean surface waters. Deep migrations and foraging at the seabed are significant parts of krill ecology, and the vertical fluxes involved in this behavior are important for the coupling of benthic and pelagic food webs and their elemental repositories.

Suspended material availability and filtration–biodeposition processes performed by a native and invasive bivalve species in streams - Carla L. Atkinson; Matt R. First; Alan P. Covich; Stephen P. Opsahl; Stephen W. Golladay (Hydrobiologia, 2011)

Associations between endogenous sex hormone levels and mammographic and bone densities in premenopausal women - Mellissa Yong; Charlotte Atkinson; Katherine M. Newton; Erin J. Aiello Bowles; Frank Z. Stanczyk; Kim C. Westerlind; Victoria L. Holt; Stephen M. Schwartz; Wendy M. Leisenring; Johanna W. Lampe (Cancer Causes & Control, 2009)

Some remarks on the occurrence, host-specificity and validity of Myxobolus rotundus Nemeczek, 1911 (Myxozoa: Myxosporea) - Kálmán Molnár; Csaba Székely; Sascha L. Hallett; Stephen D. Atkinson (Systematic Parasitology, 2009)

Effects of nonlocal turbulence on the mass transfer of dissolved species to reef corals - James L. Falter; Marlin J. Atkinson; Ryan J. Lowe; Stephen G. Monismith; Jeffrey R. Koseff (Limnology and Oceanography, 2007)
We examined the importance of nonlocal turbulence to the mass transfer of dissolved species from both cylinders and models of reef coral. Solid gypsum cylinders and gypsum‐coated model coral were dissolved in an outdoor flume at mean flow speeds of 4.5 and 10 cm s −1 . Three model corals were used: two branched forms of the genera Acropora and Pocillopora , and one lobate form of the genus Platygyra . Turbulence intensities (Tu) were measured as the ratio of the standard deviation of the time‐variant flow to the mean. Tu of between 5% and 55% were created independently of the mean flow by pumping water through two vertical arrays of jets. Mass transfer coefficients increased by 10‐70% with turbulence intensity for all forms at both mean flow speeds considered ( p

Countering morphological ambiguities: development of a PCR assay to assist the identification of Tubifex tubifex oligochaetes - Sascha L. Hallett; Stephen D. Atkinson; Jerri L. Bartholomew (Hydrobiologia, 2005)

Molecular methods clarify morphometric variation in triactinomyxon spores (Myxozoa) released from different oligochaete hosts - Sascha L. Hallett; Stephen D. Atkinson; Christer Erséus; Mansour El-Matbouli (Systematic Parasitology, 2004)